Fondaparinux versus enoxaparin in the contemporary management of non-ST-elevation acute coronary syndromes. Insights from a multicenter registry. (1st June 2021) - Almendro-Delia, Manuel; Izquierdo-Bajo, Álvaro; Madrona-Jiménez, Luis; Blanco-Ponce, Emilia; Seoane-García, Tania; García-del Río, Manuel; Carmona-Carmona, Jesús; Arboleda Sánchez, J.A.; Rodríguez Yáñez, Juan Carlos; Soto Blanco, José Manuel; Fernández García, Isabel; Castillo Caballero, José Antonio; et al.
Abstract: Background: Fondaparinux is thought to have the most favorable risk–benefit profile among all anticoagulants in non-ST-elevation acute coronary syndrome (NSTE-ACS). However, conflicting findings exist whether this holds true in current clinical practice. We aimed to assess the net clinical benefit of fondaparinux versus enoxaparin in the contemporary management of NSTE-ACS. Methods: Analysis of prospective multicenter registry data of NSTE-ACS patients who received fondaparinux or enoxaparin from February 2015, through December 2017. Survival models within a competing risks framework including site-specific random effects, were used to assess the composite of clinically relevant bleedings and major adverse cardiovascular events at 30 days. Results: Of 2094 patients, 1724 (82%) received enoxaparin and 370 (18%) fondaparinux. Both groups were comparable except for a lower prevalence of diabetes and renal impairment, and greater use of transradial approach in the fondaparinux group. Multivariate analysis revealed a net clinical benefit in favour of fondaparinux versus enoxaparin (S ubhazard Ratio [SHR] 0.59; 95%CI 0.37–0.92), mainly driven by a reduction in bleeding ( SHR 0.57; 95%CI 0.37–0.89). Exploratory analysis suggested greater reductions in bleeding with fondaparinux among patients undergoing transradial approach, revealing a significant interaction between treatment and vascular access on the multiplicative scale ( P interaction  = 0.0056), but not on an additive scale ( P  = 0.457). Propensity-score-matching analysis yielded similar results. Conclusions: In contemporary management of NSTE-ACS, fondaparinux seems to provide a favorable net clinical benefit compared with enoxaparin, primarily driven by a bleeding reduction. Effect modification on the safety profile of fondaparinux by the vascular access approach warrants further investigation. Graphical abstract: Unlabelled Image Highlights: In NSTE-ACS, fondaparinux seems to provide a net clinical benefit compared to enoxaparin, driven by a bleeding reduction. The safety profile of fondaparinux was consistent across subgroups, including those at high bleeding risk. Effect modification on bleeding reduction with fondaparinux according to the vascular access route, needs further research.